ESSENCE AND TYPES OF MONITORING (Pedagogy of Higher and Secondary Education, 2010)
in the article the maintenance, functions of a concept "monitoring" and his hands is exposed. Various approaches to the definition of essence of this concept are analysed.
Keywords: functions; monitoring; kinds of monitoring